2020
DOI: 10.3389/fonc.2020.00732
|View full text |Cite
|
Sign up to set email alerts
|

Differential O- and Glycosphingolipid Glycosylation in Human Pancreatic Adenocarcinoma Cells With Opposite Morphology and Metastatic Behavior

Abstract: Changes in the glycosylation profile of cancer cells have been strongly associated with cancer progression. To increase our insights into the role of glycosylation in human pancreatic ductal adenocarcinoma (PDAC), we performed a study on O-glycans and glycosphingolipid (GSL) glycans of the PDAC cell lines Pa-Tu-8988T (PaTu-T) and Pa-Tu-8988S (PaTu-S). These cell lines are derived from the same patient, but show an almost opposite phenotype, morphology and capacity to metastasize, and may thus provide an attrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(47 citation statements)
references
References 85 publications
5
42
0
Order By: Relevance
“…Importantly, the sialylated Tn antigen was notably decreased by TGF-β stimulation in Patu-S cells, which is believed to be carried by various glycoproteins and be associated with cancer progression, invasion and metastasis in some published studies (81,82). In line with this TGF-β-induced downregulation, we have also observed the loss of sialylated Tn antigen in the mesenchymal-like Pa-Tu-8988T (PaTu-T) cells (83), which was derived from the same was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…Importantly, the sialylated Tn antigen was notably decreased by TGF-β stimulation in Patu-S cells, which is believed to be carried by various glycoproteins and be associated with cancer progression, invasion and metastasis in some published studies (81,82). In line with this TGF-β-induced downregulation, we have also observed the loss of sialylated Tn antigen in the mesenchymal-like Pa-Tu-8988T (PaTu-T) cells (83), which was derived from the same was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Discussionsupporting
confidence: 80%
“…The neo-expression of globosides with TGF-β treatment is an interesting observation, since it has been reported that Gb3 is associated with tumor metastasis and invasion in many cancers, including lung cancer (86), colon cancer (87,88), breast cancer (89), gastric adenocarcinomas (90), and pancreatic cancer (91). In our previous study, globoside Gb3 and Gb4 were specifically expressed in the mesenchymal-like PaTu-T cells compared to PaTu-S cells (83). Again, these findings indicate the globosides may contribute to the invasion and metastasis in PDAC.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Furthermore, it is known that alteration of glycosylation on lipids at the cell surface can affect cell adhesion, recognition, and signal transduction [ 27 , 28 ] through the regulation of different signaling pathways involved during EMT. The EMT-associated alteration of glycosphingolipids (GSLs) has been identified in several cancer types; e.g., reduced globosides and enhanced gangliosides in mesenchymal-like PaTu-T cells compared to epithelial-like PaTu-S cells have been detected using mass spectrometry-based glycomics and flow cytometry [ 29 ], the functional loss of globosides induces EMT in ovarian cancer using the CRISPR- Cas9 approach [ 30 ], or during transition of breast cancer stem cells [ 31 ]. In addition, the emerging role of GSLs in epithelial-to-mesenchymal transition (EMT) was previously mentioned as a process that enables metastatic cellular invasion in the context of cancer progression, highlighting the spontaneous and transforming growth factor β (TGFβ)-induced alterations of GSLs [ 32 ].…”
Section: Introductionmentioning
confidence: 99%